EVALUASI SIFAT-SIFAT KIMIA TANAH YANG DIAPLIKASI LIMBAH CAIR PABRIK KELAPA SAWIT DI PT SMART KEBUN PADANG HALABAN KABUPATEN LABUHAN BATU UTARA - Mhd Arian Torang; Abdul Rauf; Purba Marpaung (Universitas Sumatera Utara, 2013)
Liquid Waste of Oil Palm Factory contains nutrients which are required by plants and it can beapplied to the estate crops. This research evaluate the palm oil factory soil chemical applied byliquid waste of oil palm factory at PT Smart Padang Halaban Plantation at Labuhan Batu UtaraDistrict. Soil sampel by using soil sampling method at three different location of research namelycontrol, sela and rorak aplications, six deepness level and three times replicates. Parameters thatmeasured are pH, C, N, C/N and absorption P of plant. Statistical test that used is determined flatvalue and criteria characteristic of soil. The result of research showed they increasing ofcharacteristic chemistry which are apllicated by liquid waste of oil palm factor. Parameters whichexperience increasing is pH, C, N, C/N and absorption P of plant.Keywords : evaluation, characteristics chemistry of soil, liquid waste of oil palm